Equatorial and low-latitude positive ionospheric phases due to moderate geomagnetic storm during high solar activity in January 2013 - Ribeiro (My University, 2019)
The day-to-day variability of the equatorial and low-latitude ionosphere during quiet and disturbed periods is one of the ionospheric highlighted Space Weather research topics, particularly the ionospheric electrodynamics during geomagnetic storms. This study investigates the response of ionospheric F-region from the equatorial region to beyond the Equatorial Ionization Anomaly (EIA) crest during moderate geomagnetic storm (minimum Dst = 53 nT) that took place on January 17 to 18, 2013, during the high solar activity period of solar cycle 24. The Total Electron Content (TEC) obtained through a network of 82 dual frequency GPS receivers, spanning over an area of 30 30 in latitude and longitude are used. Also the F-layer virtual height (h’F) and critical frequency (foF2) observations from 3 ionosondes, in the South American sector are used. Specifically, these GPS-TEC receivers and ionosondes are used to investigate how the F-layer was disturbed by two positive ionospheric phases occurred during the aforementioned disturbed period. The first positive ionospheric phase was probably due to a travelling ionospheric disturbance (TID). When this TID reached the Brazilian coast at low-latitude, the EIA crest was in the growth phase and makes it challenging to separate the spatial-temporal evolution of both phenomena. The second positive ionospheric phase was caused by an anomalous nighttime equatorial positive ionospheric cloud travelling from the east sector towards the west sector. In addition, how the EIA was disturbed by these two positive ionospheric phases in the eastern and western Brazilian sectors is also investigated.
Keywords: Geomagnetic storms; Solar activity; Space weather; TEC; Total electron content; Geomagnetic storm; Equatorial and low latitude; F-layer Ionospheric positive phase